Forecasting throuth the rear-view mirror: Data revisions and bond return predictability - Eric Ghysels; Casidhe Horan; Emanuel Moench (Federal Reserve Bank of New York, 2012)
Real-time macroeconomic data refl ect the information available to market participants, whereas fi nal data-containing revisions and released with a delay-overstate the information set available to them. We document that the in-sample and out-of-sample Treasury return predictability is signifi cantly diminished when real-time as opposed to revised macroeconomic data are used. In fact, much of the predictive information in macroeconomic time series is due to the data revision and publication lag components.
Keywords: G10; G12; 330; return predictability; real-time data; dynamic factor models